Multimodal imaging in constrictive pericarditis: a case report of cardiac cirrhosis - Barriales-Revilla, Lucía (2023)
Constrictive pericarditis is a rare cause of ascites and cardiac cirrhosis. We present the case of a 36-year- old male patient with a history of cirrhosis of unknown etiology, who consulted for refractory ascites, dyspnea, and lower limb swelling. Echocardiography determined constrictive pericarditis, which was corroborated by the findings of computed tomography. The clinical and hemodynamic worsening of the patient led to an emergency pericardiectomy with satisfactory recovery. This report shows a severe clinical consequence of constrictive pericarditis, cardiac cirrhosis, which was reversible with pericardial extirpation. Multimodal imaging was essential in the diagnosis of constrictive pericarditis.